(3CQHYhf MOjkKG aj JQc GdXdes - (3YHO Gddg Hf Ydj Hf YHO GdQMef ShjOGf GdOedjLj,J (B1234 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CeQ YHGOg HGdYOd hGdEMSGf hHYO ajbhd YHO Gddg Hf Ydi ShjOGf gPg CQHYhf MOjKkG ef GdSfI GdZQg bUOJ HgG HPd fUjMI GdCeI ajeG hbY ai gPg GdCReGf ef cKQI GdXde s
(3BNQgG (B:s
(3GdCQHYhf KdGKI dGJQO OYhJge GdEeGe GdYGOd hGdUGFe MJi jaWQ hOYhg GdeXdhe QhGg GdEeGe CMeO hGdJQePi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B13s
(3GdfSNI HgG MhGTs
(3MOjKs
(3HgG fXGe GdJYbjHI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B107 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B89s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs